The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/gj.3241
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term evolution of the Doruneh Fault region (Central Iran): A key to understanding the spatio‐temporal tectonic evolution in the hinterland of the Zagros convergence zone

Abstract: A better understanding of intraplate deformation requires the knowledge of the space–time scales involved in its development and to decipher possible links with the dynamic evolution of the plate boundaries. Central Iran provides an ideal test site to approach this scientific issue, since it is characterised by a prolonged history of Mesozoic–Cenozoic intraplate deformation that has been interfering with the spatio‐temporal re‐organization of the Zagros convergence zone along the Eurasia plate boundary. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 140 publications
(497 reference statements)
2
25
0
Order By: Relevance
“…(Fig. 15a to 15c), as demonstrated elsewhere (Koyi et al, 2016;Tadayon et al, 2018). Vertical axis rotations favor a progressive change from transpressive to more purely compressive.…”
Section: Mio-pliocene To Early Quaternary Strain Partitioningsupporting
confidence: 72%
“…(Fig. 15a to 15c), as demonstrated elsewhere (Koyi et al, 2016;Tadayon et al, 2018). Vertical axis rotations favor a progressive change from transpressive to more purely compressive.…”
Section: Mio-pliocene To Early Quaternary Strain Partitioningsupporting
confidence: 72%
“…Topographic growth should have also occurred along the western Alborz Mountains, although it should be noted that the northern sectors of the range must have represented a topographic barrier between Central Iran and the Caspian Sea since the early Eocene as suggested by the spatial distribution of Karaj Formation (Figure 1; Guest, Axen et al., 2006). The post 38‐36 Ma contractional deformation and associated erosional cooling may represent the earliest stages of late Eocene‐early Oligocene collisional deformation recorded across the entire Arabia‐Eurasia collision zone from the Zagros to the Caucasus, Talesh, Alborz and Kopeh Dagh mountains (Ballato et al, 2011, 2015; Morley et al., 2009; Mouthereau et al., 2012; Rezaeian et al., 2012; Roberts et al., 2014; Tadayon et al., 2018; S. J. Vincent et al., 2007). Sedimentation resumed not later than 16.2 Ma (see next section), therefore between 38 and 36 Ma and not later than 16.2 Ma, the Tarom Basin must have experienced erosion and nondeposition in association with external drainage conditions (Figure 14a).…”
Section: Discussionmentioning
confidence: 99%
“…From analogue model experiments, oblique fold patterns occurred in transpressive/strike-slip shear zones (Richard, 1991). The amount of rotation evolves through time if a function of the mode of transpression (pure/simple shear, Fossen et al, 1994), as demonstrated elsewhere (Tadayon et al, 2018). In figure 15, we draw the simplified fold axis to help the reader.…”
Section: C7mentioning
confidence: 97%